2021
DOI: 10.1101/2021.07.29.454227
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Increasing cell size remodels the proteome and promotes senescence

Abstract: Cell size is tightly controlled in healthy tissues, but it is poorly understood how cell size affects cell physiology. To address this, we measured how the proteome changes with cell size. Protein concentration changes are widespread, depend on the DNA-to-cell size ratio, and are predicted by subcellular localization, size-dependent mRNA concentrations, and protein turnover. As proliferating cells grow larger, concentration changes associated with cellular senescence are increasingly pronounced, suggesting tha… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
90
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(103 citation statements)
references
References 59 publications
13
90
0
Order By: Relevance
“…This is in line with recent work in yeast, which shows that an increase in cell volume beyond a particular point causes ‘cytoplasmic dilution’ and permanent cell-cycle exit (Neurohr et al ., 2019). More recent work in mammalian cells also indicates that increasing cell size itself results in proteomic changes that gradually approach those found in senescent cells, supporting our hypothesis that cellular growth signalling that drives an increase in cell size per se promotes senescence (Lanz et al ., 2021). Interestingly, this study shows that an increase in cell size promotes senescence in cells where the cell cycle is arrested via the CDK4/6 inhibitor palbociclib.…”
Section: Discussionsupporting
confidence: 86%
“…This is in line with recent work in yeast, which shows that an increase in cell volume beyond a particular point causes ‘cytoplasmic dilution’ and permanent cell-cycle exit (Neurohr et al ., 2019). More recent work in mammalian cells also indicates that increasing cell size itself results in proteomic changes that gradually approach those found in senescent cells, supporting our hypothesis that cellular growth signalling that drives an increase in cell size per se promotes senescence (Lanz et al ., 2021). Interestingly, this study shows that an increase in cell size promotes senescence in cells where the cell cycle is arrested via the CDK4/6 inhibitor palbociclib.…”
Section: Discussionsupporting
confidence: 86%
“…Nearly all proteins (3132/3171, 99%) displayed a relative change between -1 and 1, indicating that concentrations maximally halve or double when cells double in size as within a normal cell cycle. This scaling analysis confirmed the previously observed dilution of the retinoblastoma protein RB1 (3) as well as histones (16). Unexpectedly, these proteins were neither unique nor the most diluted ones.…”
Section: Introductionsupporting
confidence: 89%
“…Consistent with the proteomics data, we observed dilution of RB1, MCM2 as well as RPL9 as a representative of the ribosomal subunits within the ~2-fold average volume differences between the smallest and largest subpopulations. It has been reported that RB1 and histone concentrations are transcriptionally regulated (3,16), but whether the overall proteome scaling is transcriptionally regulated is not known. To test this, we analysed scaling using NCI60 RNAseq data (15) and compared this to the proteome scaling.…”
Section: Introductionmentioning
confidence: 99%
“…In line with accelerated cell aging, HF-MSS showed a downregulation of histone proteins, a well-recognized sign of senescence [28]. Importantly, one of the key features of senescent cells is their increased size [29]. These results, and the fact that the HF-MSS proliferation rate was reduced, suggest that these cells achieve a sort of senescent state in order to survive.…”
Section: Discussionmentioning
confidence: 80%